Collective bargaining agreement with DLSU Employees Association - De La Salle University, Manila (Animo Repository, 1986)
On December 23, 1986, the University entered into a collective bargaining agreement with DLSU Employees Association. The agreement was for 3 years, until 22 December 1989.